2017
DOI: 10.1002/pssa.201600582
|View full text |Cite
|
Sign up to set email alerts
|

Structural and electrical properties of InAs/GaSb superlattices grown by metalorganic vapor phase epitaxy for midwavelength infrared detectors

Abstract: InAs/GaSb superlattice (SL) structures were fabricated on GaSb substrates by metalorganic vapor phase epitaxy (MOVPE) toward midwavelength infrared (MWIR) photodiodes. Almost defect‐free 200‐period SLs with a strain‐compensation interfacial layer were successfully fabricated and demonstrate an intense photoluminescence peak centered at 6.1 µm at 4 K and an external quantum efficiency of 31% at 3.5 µm at 20 K. These results indicate that the high‐performance MWIR detectors can be fabricated in application with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In addition, Li et al [160,161] selected As 0.1 Sb 0.9 interfaces over InAsSb as an option to compensate the strain of the SLs on the GaSb substrate, which achieved a smooth surface with an root mean square (RMS) roughness of 0.7 nm and strong absorption coefficient in the MWIR region. Arikata et al [162] demonstrated LWIR T2SLs by applying simple InSb interface layers grown at 500 • C, which addressed the in-plane unbalanced strain, obtaining defect-free 200-period SLs with an intense PL peak at 6.1 µm and an external QE of 31% at 3.5 µm. Moreover, InAs substrates, known to have a lower absorption coefficient in the MWIR/LWIR regimes than GaSb substrates, were introduced to the MOCVD growth of strainbalanced InAs/GaSb T2SLs by Huang's group [163]; a GaAslike interface was utilized in order to compensate for the compressive strain originating from the GaSb layer.…”
Section: Growth Of Inas/gasb T2slsmentioning
confidence: 99%
“…In addition, Li et al [160,161] selected As 0.1 Sb 0.9 interfaces over InAsSb as an option to compensate the strain of the SLs on the GaSb substrate, which achieved a smooth surface with an root mean square (RMS) roughness of 0.7 nm and strong absorption coefficient in the MWIR region. Arikata et al [162] demonstrated LWIR T2SLs by applying simple InSb interface layers grown at 500 • C, which addressed the in-plane unbalanced strain, obtaining defect-free 200-period SLs with an intense PL peak at 6.1 µm and an external QE of 31% at 3.5 µm. Moreover, InAs substrates, known to have a lower absorption coefficient in the MWIR/LWIR regimes than GaSb substrates, were introduced to the MOCVD growth of strainbalanced InAs/GaSb T2SLs by Huang's group [163]; a GaAslike interface was utilized in order to compensate for the compressive strain originating from the GaSb layer.…”
Section: Growth Of Inas/gasb T2slsmentioning
confidence: 99%
“…[117] Razeghi et al [118] used diluted AsH 3 for the MOCVD growth of the InAsSb layer and pure AsH 3 for the InAs layer at a low V/III ratio to enhance Sb incorporation. Although significant work and progress have been made in the growth of InAs/GaSb and InAs/InAsSb T2SL materials and devices by MBE [102,116,[119][120][121][122][123] and MOCVD, [107,[124][125][126][127][128][129][130] growth of barrier structures is generally challenging because barrier structures usually contain Al-material such as AlSb, AlAs, or AlAsSb, and Al-containing materials are challenging to grow and susceptible to oxidation during both growth and processing stages. The absence of Al-based barriers could also be associated with the fact that although the lattice mismatches, within the 6.1 A family of InAs, GaSb, and AlSb are small, they are not negligible particularly at high growth temperatures.…”
Section: Materials Growth Of Inas/gasb and Inas/inassb T2slmentioning
confidence: 99%
“…18,19) High-performance devices based on InAs=GaAs T2SLs were grown by molecular beam epitaxy (MBE), [20][21][22][23] and there have been reports on trials of InAs=GaSb grown by the metal organic vapor phase epitaxy (MOVPE) method. [24][25][26][27] In recent years, InAs=GaSb T2SL has been grown by production-scale MOVPE with qualities and device performances close to those grown by MBE. 28) On the other hand, lattice matching to the substrate is an important issue to increase the number of superlattices aiming at high sensitivity.…”
Section: Introductionmentioning
confidence: 99%